2017
DOI: 10.1186/s13071-017-2218-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the neuropeptide content of Biomphalaria ganglia nervous system following Schistosoma infection

Abstract: BackgroundMolluscs, including snails, are prone to parasite infection, which can lead to massive physiological and behavioural changes, yet many of the molecular components involved remain unresolved. Central to this point is the neural system that in snails consists of several ganglia that regulate the animals’ physiology and behaviour patterns. The availability of a genomic resource for the freshwater snail Biomphalaria glabrata provides a mean towards the high throughput analysis of changes in the central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 82 publications
(84 reference statements)
1
27
0
Order By: Relevance
“…Schistosome parasites have a direct impact on their snail intermediate hosts; as they grow and generate cercariae, sporocysts deplete galactogen in the albumen gland and consume the ovotestis and hepatopancreas, converting stored glycogen to glucose [11, 12]. Wang et al [40] found that neuropeptides and precursor proteins involved in snail reproduction were heavily downregulated in infected prepatent snails compared to uninfected snails, suggesting that this could play a role in castration of Biomphalaria snails by schistosomes. Other downregulated neuropeptides in prepatent snails were linked to snail feeding and growth, process that directly impact the reproductive capacity, metabolism and immunity of the snail host.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosome parasites have a direct impact on their snail intermediate hosts; as they grow and generate cercariae, sporocysts deplete galactogen in the albumen gland and consume the ovotestis and hepatopancreas, converting stored glycogen to glucose [11, 12]. Wang et al [40] found that neuropeptides and precursor proteins involved in snail reproduction were heavily downregulated in infected prepatent snails compared to uninfected snails, suggesting that this could play a role in castration of Biomphalaria snails by schistosomes. Other downregulated neuropeptides in prepatent snails were linked to snail feeding and growth, process that directly impact the reproductive capacity, metabolism and immunity of the snail host.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosome parasites have a direct impact on their snail intermediate hosts: as they grow and generate cercariae, sporocysts deplete galactogen in the albumen gland and consume the ovotestis and hepatopancreas, converting stored glycogen to glucose [10,35]. Wang and colleagues [36] found that neuropeptides and precursor proteins involved in snail reproduction were heavily down regulated in infected prepatent snails compared to uninfected snails, suggesting that this could play a role in castration of Biomphalaria snails by schistosomes. Other down regulated neuropeptides in prepatent snails were linked to snail feeding and growth, process that directly impact the reproductive capacity, metabolism and immunity of the snail host.…”
Section: Discussionmentioning
confidence: 99%
“…Myomodulins are neurotransmitters involved in regulating feeding behavior by controlling radula protractor muscles used for feeding [62] in Lymnaea stagnalis [63] and Aplysia californica [64]. Myomodulin is down-regulated in prepatent S. mansoni-infected B. glabrata and this was implicated as possibly diminishing feeding efficiency in infected snails [65]. Down-regulation of a B. pfeifferi feeding circuitry peptide was seen in early and patent S. mansoni infections [23].…”
Section: Shared Response Of Two Biomphalaria Species To a Sublethal Dmentioning
confidence: 99%